2016
DOI: 10.3389/fpls.2016.01312
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Expression Analyses Reveal Important Roles for Plant PKS III Family during the Conquest of Land by Plants and Angiosperm Diversification

Abstract: Polyketide synthases (PKSs) utilize the products of primary metabolism to synthesize a wide array of secondary metabolites in both prokaryotic and eukaryotic organisms. PKSs can be grouped into three distinct classes, types I, II, and III, based on enzyme structure, substrate specificity, and catalytic mechanisms. The type III PKS enzymes function as homodimers, and are the only class of PKS that do not require acyl carrier protein. Plant type III PKS enzymes, also known as chalcone synthase (CHS)-like enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…More studies suggested that blue light should be recommended as a supplementary light source for accumulation of phenols and flavonoids [84, 85]. Moreover, the promotion of primary metabolism partly promoted contents of phenols and flavonoids in the LED-mix treatment (Table 3), since the products of primary metabolism are utilized to synthesize a wide range of secondary metabolites through the shikimate pathway, mevalonic acid pathway, and methylerythritol 4-phosphate (MEP) pathway in higher plants [8689]. Results from Zhao et al [90] showed that enhanced accumulation of most secondary metabolites by elevated temperature is possibly due to increased contents of chlorophyll, sugar, and starch in Robinia pseudoacacia seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…More studies suggested that blue light should be recommended as a supplementary light source for accumulation of phenols and flavonoids [84, 85]. Moreover, the promotion of primary metabolism partly promoted contents of phenols and flavonoids in the LED-mix treatment (Table 3), since the products of primary metabolism are utilized to synthesize a wide range of secondary metabolites through the shikimate pathway, mevalonic acid pathway, and methylerythritol 4-phosphate (MEP) pathway in higher plants [8689]. Results from Zhao et al [90] showed that enhanced accumulation of most secondary metabolites by elevated temperature is possibly due to increased contents of chlorophyll, sugar, and starch in Robinia pseudoacacia seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate these two hypotheses, we performed a phylogenetic analysis using PKS amino acid sequences to link their syntenic cluster membership with sequence divergence reflected in the phylogenetic tree. The analysis incorporated sequences from over 180 species thereby dramatically extending previous phylogenetic analyses on the type III PKS (41). Here, we included 1,607 different amino acid sequences and obtained detailed phylogenetic relationships using the Maximum likelihood method ( Figure 5), it seems likely that the 'R-4-C'-type genes in the syntenic clusters originated from the same evolutionary event by duplication/triplication events.…”
Section: Phylogenetic Analysis Indicates Timing Of the Appearance Of mentioning
confidence: 99%
“…OsLAP6 , also called OsPKS1 (Wang et al 2013 ), encodes a plant PKS III superfamily protein, which catalyzes the synthesis of various plant secondary metabolites (Xie et al 2016 ). Secondary metabolites are involved in regulating a variety of developmental processes in plants, such as disease resistance, environmental stress response, and sexual reproduction (Wink 1988 ; Kliebenstein 2004 ; Gershenzon 1984 ; Galambosi et al 2009 ; Theis and Lerdau 2003 ).…”
Section: Discussionmentioning
confidence: 99%